Neurofeedback in ADHD: further pieces of the puzzle - Gevensleben, Holger; Kleemeyer, Maike; Rothenberger, Lillian Geza; Studer, Petra; Flaig-Roehr, Andrea; Moll, Gunther; Rothenberger, Aribert; Heinrich, Hartmut (Brain Topography, 2014)
Among the different neuromodulation techniques, neurofeedback (NF) is gaining increasing interest in the treatment of children with attention-deficit/hyperactivity disorder (ADHD). In this article, a methodological framework is summarised considering the training as a neuro-behavioural treatment. Randomised controlled trials are selectively reviewed. Results from two smaller-scale studies are presented with the first study comprising a tomographic analysis over the course of a slow cortical potential (SCP) training and a correlational analysis of regulation skills and clinical outcome in children with ADHD. In the second study, ADHD-related behaviour was studied in children with tic disorder who either conducted a SCP training or a theta/low-beta (12-15 Hz) training (single-blind, randomised design). Both studies provide further evidence for the specificity of NF effects in ADHD. Based on these findings, a refined model of the mechanisms contributing to the efficacy of SCP training is developed. Despite a number of open questions concerning core mechanisms, moderators and mediators, NF (theta/beta and SCP) training seems to be on its way to become a valuable and ethically acceptable module in the treatment of children with ADHD.
EVALuna2:23870